Health Benefits of Integrating Physical Activity into Our Day-to-Day Lives - Aggarwal, Rashmi (Journal of Social Health and Diabetes, 2018)
In the 21st century it is the sedentary lifestyle that is responsible for causation of the dual epidemic of obesity and type 2 diabetes. Incorporating physical activity into our daily lives will not only improve our physical health but also enhance our mental and neurocognitive functions. Regular physical activity reduces the risks of developing metabolic derangements such as overweight, hypertension, different types of diabetes, metabolic syndrome, nonalcoholic fatty liver disease, osteoporosis, and certain types of organ-specific cancers.
Keywords: physical activity; hypertension; metabolic syndrome; diabetes